EFFECT OF TIMING SLASHING, BURNING AND SOIL AMENDMENT ON SOIL MICROBES - Nwokeh, U. J.; Nwachukwu, S. C.; Onwuka, M. I. (FUDMA JOURNAL OF SCIENCES, 2023)
Various challenges face the sustainability of soil ecosystem. This research was carried out to assess the impact of burning and application of cow dung on soil microbes. Soil samples were taken from three different locations: Afugiri, Lodu and Umudike. The study comprised of two experiments. The focus of the first experiment was to check the effect of slash and burn on soil pH, organic matter, microbial biomass phosphorus (MBP) and soil microbes. Result obtained showed that burning affected soil pH, organic matter and MBP and microbial population. Burning reduced the organic matter content of soil, and increased soil pH. The results of the microbial biomass showed that burning was disadvantageous to the sustainability of soil ecosystem. However, in the second experiment, cowdung and fortified cowdung amendment were applied to determine the effect of organic amendment on soil microbes. Cowdung significantly affected bacteria population and number of earthworm species. Bacterial species have more population than fungal species. The results from this study indicate that burning in agricultural land increases soil pH, but have the capacity to destroy beneficial microbes and reduce those activities carried out by them.